2014
DOI: 10.1071/cp13283
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fixation and symbiosis-induced accumulation of mineral nutrients by cowpea (Vigna unguiculata L. Walp.)

Abstract: Little information currently exists on the relationship between rhizobial symbiosis and mineral accumulation in nodulated legumes. The aim of this study was to measure fixed nitrogen (N) in whole plants and in young fully expanded trifoliate leaves of cowpea genotypes, and to relate this to mineral accumulation in the leaves. The data revealed marked differences between high and low N2-fixing genotypes, with the former consistently showing greater %N, plant or leaf total N, and amount of N fixed compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…Another factor that seems to define the level of mineral accumulation in nodulated legumes is the symbiotic efficiency of N 2 -fixing bacteria in root nodules. It has been shown that high N 2 -fixing legumes generally tend to accumulate more nutrient elements in shoots than their lowfixing counterparts (Belane et al, 2014). In this study, genotypes such as Apagbaala, Fahari, Iron Gray, Line 2020, Bengsogla and Omondaw, which accumulated significantly high concentrations of trace elements in leaves and seed, were earlier reported to be high N 2 -fixers, and to accumulate large amounts of symbiotic N in their biomass Dakora, 2009, 2010).…”
Section: Trace Element Density In Cowpea Leaves and Seedsmentioning
confidence: 60%
See 1 more Smart Citation
“…Another factor that seems to define the level of mineral accumulation in nodulated legumes is the symbiotic efficiency of N 2 -fixing bacteria in root nodules. It has been shown that high N 2 -fixing legumes generally tend to accumulate more nutrient elements in shoots than their lowfixing counterparts (Belane et al, 2014). In this study, genotypes such as Apagbaala, Fahari, Iron Gray, Line 2020, Bengsogla and Omondaw, which accumulated significantly high concentrations of trace elements in leaves and seed, were earlier reported to be high N 2 -fixers, and to accumulate large amounts of symbiotic N in their biomass Dakora, 2009, 2010).…”
Section: Trace Element Density In Cowpea Leaves and Seedsmentioning
confidence: 60%
“…Similarly, at Manga in the Sudano-Sahelian savanna of Ghana, leaf protein levels varied from 24 to 35%, with 12 out of 30 genotypes recording more than 30% protein in their leaves (Figure 3). The leaves of N 2 -fixing legumes such as cowpea are very rich in N due to the species ability to reduce N 2 into NH 3 and subsequently into nitrogenous solutes for plant use (Belane et al, 2014). In plants, N is required for the synthesis of macromolecules such as chlorophyll needed for harvesting light photon energy during photosynthesis and formation of the enzyme ribulose-1,5-bisphosphate carboxylaseoxygenase (Rubisco), which reduces CO 2 during photosynthesis.…”
Section: Leaf and Seed Protein Of Cowpea Genotypesmentioning
confidence: 99%
“…Fertilizer production is an energy intensive process and even in highly mechanized agricultural systems of the US Corn Belt, energy resulting from fertilizer production is >30 % of farm energy use in rain-fed maize systems (Kim et al 2009). Assuming a cowpea seed yield of 820 kg ha −1 (Kaizzi et al 2007) and seed N content of 4 % (Tagoe et al 2010), sale of cowpea seed removes 16.4 kg N ha −1 of the N fixed during the (Belane et al 2014), the remaining root and shoot biomass would provide on the order of 7-75 kg N ha −1 to the field or for use as animal fodder. The benefits of legumes in rotation need to be qualified; however, because they assume that farmers have access to cowpea seeds, can generate a significant return when planting cowpea, and have a place to market cowpea; this may be a large assumption for many farmers in Africa.…”
Section: Economic Feasibility Of Management Alternativesmentioning
confidence: 99%
“…Recent work with Vigna unguiculata L. Walp. [19] indicated that as root nodule number and weight increased, the expected increase in Rhizobia-fixed nitrogen was associated with a concomitant increase in a majority of other rhizosphere-derived essential mineral elements in the leaf tissue. If this strong relationship between endosymbiont nitrogen-fixation and general mineral accumulation in legumes is similar in cycads, the implications of our results are of critical importance to conservation managers.…”
Section: Discussionmentioning
confidence: 99%